UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DENGAN MODEL SCIENCE, TECHNOLOGY AND SOCIETY PESERTA DIDIK PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS IV SDN TAMPOJUNG TENGGINA: EFFORTS TO IMPROVE CRITICAL THINKING SKILLS WITH THE SCIENCE, TECHNOLOGY AND SOCIETY MODEL OF STUDENTS IN SOCIAL SCIENCE SUBJECTS GRADE IV SDN TAMPOJUNG TENGGINA - Ramadhani, Dzkri Wahyu; Setyawan, Agung (CV. Kalimasada Group, 2023)
This study looks at how well the creativity of fourth grade social studies students of Tampojung Tenggina Elementary School is enhanced by the Science, Technology and Society (STS) learning paradigm. The research was conducted in two cycles with a classroom action research (CAR) approach. Each cycle includes planning, implementation, observation, and reflection, with modifications made in response to teacher observations. Students' capacity to connect academic ideas with real-world situations was enhanced during the first cycle as they worked together in groups to examine the relationship between natural resources and local economic growth. By linking natural resources to economic expansion, the second cycle further strengthened their understanding while fostering their critical thinking and creative abilities. These results are consistent with previous studies on how well STS models improve learning outcomes and process skills. Nonetheless, this study uses SITS in a novel way to promote critical thinking in social studies, demonstrating its efficacy as a method of combining classroom teaching with real-world situations.